Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.5194/acp-23-471-2023
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ash, water vapor, and heterogeneous chemistry on the evolution of a Pinatubo-size volcanic cloud

Abstract: Abstract. We employ the ECHAM5/MESSy2 atmospheric chemistry general circulation model (EMAC) that incorporates calculations of gas-phase and heterogeneous chemistry coupled with the ozone cycle and aerosol formation, transport, and microphysics to calculate the 1991 Pinatubo volcanic cloud. We considered simultaneous injections of SO2, volcanic ash, and water vapor. We conducted multiple ensemble simulations with different injection configurations to test the evolution of SO2, SO42-, ash masses, stratospheric … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 134 publications
1
6
0
Order By: Relevance
“…(2020) also reported in a simulation of Kelut that SO 2 may undergo heterogeneous reactions on ash while Abdelkader et al. (2023) suggest that injected water vapor can enhance stratospheric OH. Such effects are not included in our simulations, but they might have resulted in a loss of SO 2 more rapid than in our simulations.…”
Section: Conclusion and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…(2020) also reported in a simulation of Kelut that SO 2 may undergo heterogeneous reactions on ash while Abdelkader et al. (2023) suggest that injected water vapor can enhance stratospheric OH. Such effects are not included in our simulations, but they might have resulted in a loss of SO 2 more rapid than in our simulations.…”
Section: Conclusion and Discussionmentioning
confidence: 83%
“…Further work is necessary to quantify the magnitude of this effect in smaller eruptions in the satellite record or in larger historical eruptions, like in Clyne et al (2021). Zhu et al (2020) also reported in a simulation of Kelut that SO 2 may undergo heterogeneous reactions on ash while Abdelkader et al (2023) suggest that injected water vapor can enhance stratospheric OH. Such effects are not included in our simulations, but they might have resulted in a loss of SO 2 more rapid than in our simulations.…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…The results of Abdelkader et al. (2023) revealed a doubling of the radiative effect in the SW and LW when considering ash aging in climate simulations of Pinatubo‐size eruptions. Zhu et al.…”
Section: Introductionmentioning
confidence: 97%
“…Their simulations showed that the volcanic cloud rises by 1 km/day during the first week, primarily due to the ash-induced heating and lofting. The results of Abdelkader et al (2023) revealed a doubling of the radiative effect in the SW and LW when considering ash aging in climate simulations of Pinatubo-size eruptions. Zhu et al (2020) showed that the ash particles controlled the chemistry and optical properties of volcanic clouds in the first days to weeks after the Mt.…”
mentioning
confidence: 94%
“…The long‐term evolution of stratospheric volcanic clouds is sensitive to the height of emissions. The vertical distribution of volcanic material shapes the intense dynamic, chemical, and microphysical processes in a volcanic cloud (Abdelkader et al., 2022; Stenchikov, 2021). The satellite observations available at the time of the Mt.…”
Section: Introductionmentioning
confidence: 99%